Green Hotel Practices: Perspectives of Domestic and International Travelers (IUBAT Review, 2025)
The hospitality industry is becoming more practiced in sustainable development, and green hotel practice is integral to it globally. The research examines the attitude of local and international tourists toward green hotel practices in Bangladesh. The primary purpose is to discover awareness, motivation, perceived benefits, and obstacles to implementing green hotel practices in Bangladesh. The study aims to establish the attitude of visitors towards green hospitality services and how these attitudes can guide policy and operational interventions in the future. We collected primary data from 90 respondents using a structured questionnaire to achieve these objectives. Using purposive non-probability sampling, we selected a sample of respondents from eight eco-friendly hotels in Dhaka. Data analysis was done using Microsoft Excel and SPSS version 26. The results indicate that both domestic and international tourists know the importance of green hotel practices, with slightly more awareness among international tourists.The strongest reasons for adopting this policy are environmental protection, cost savings through energy savings, and brand image reinforcement. However, the most significant limitations of extensive application are excessive implementation cost, unawareness, and insufficient institutional support. The study concludes that assistance with guest education, economic incentives, and other policy assistance can play an essential role in hotels adopting sustainable practices. The findings are of maximum importance for policymakers, hoteliers, and greens concerned with formulating sustainable tourism for emerging economies like Bangladesh.IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 113-144